The Impact of New Free Trade Agreements on Incumbent Firms and Workers - Harald Dale-Olsen (Institute of Labor Economics (IZA), 2023)
Trade policies might affect firms' market power and their ability to reap product-market mark-ups. Thus, potentially they influence not only firms' economic performance, but also worker pay. Utilising panel-data on Norwegian Manufacturing exporters from 2005-18 and multi-product production function-estimation techniques and recent development within the literature on dynamic treatment effects in event studies with heterogeneous treatment effects, we show that free-trade agreements increase exports and return-on-assets for Norwegian incumbent exporters, but their mark-ups decline. On average, workers in these established firms benefit from free-trade agreements, but this depends on occupations, union strength and labour market tightness.
Keywords: D24; F14; L11; J31; J42; 330; free-trade agreements; price-cost markups; profits; wages; multiproduct-function-estimation; dynamic treatment effects